AKOMODASI KEARIFAN LOKAL PADA PERATURAN DESA TENTANG BADAN USAHA MILIK DESA DI KABUPATEN BANYUMAS - Fatni Erlina (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
The purpose of this study is to determine whether changes in the position, rights and authority of villages, after the issuance of Village Law number 6 of 2021, have a positive correlation with village local wisdom discourse. The village government, and BPD have an important position in determining the direction of village development policy, through the village budget function. The Village Law has given wider authority to village governments, but few villages have paid attention to the existence of local wisdom. The importance of this research, because local wisdom reflects a cultural value, and national identity, born alive and grew up in a homogeneous environment of village communities. This research was conducted through a village budget survey, in Banyumas Regency. The results show that most villages do not give enough budget priority, in preserving the village's local wisdom. BUMDes mostly prioritize profit, without considering the value, existence and uniqueness possessed as characteristics of the village.